2003
DOI: 10.4028/www.scientific.net/kem.240-242.817
|View full text |Cite
|
Sign up to set email alerts
|

Radiostereoanalysis of Press-Fit Cups with Alumina Liner. A Randomized Clinical Trial

Abstract: The purpose of the present study was to assess the in-vivo migration of a press-fit acetabular component in total hip arthroplasty using alumina or polyethylene liners. The measurements were performed using radiostereometric analysis (RSA). Fifty patients (50 hips) with degenerative hip osteoarthritis were randomized in two groups. All received a modular press-fit cup and an alumina head. In 27 cases we used a polyethylene, in 23 an alumina liner. RSA was performed for a followup of 2 years after surgery. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…A study flow diagram depicting the identification of the studies is shown in Figure 1. We identified a total of 1697 potential articles (450 from PubMed; 546 from Embase; 52 from CENTRAL; 631 from Web of Science; and 18 from the reference lists), of which 13 studies including a total of 2,488 THAs fulfilled the inclusion criteria for final review (9, 15-16-17, 19-20-21-22-23-24-25-26-27). The characteristics of the included studies are shown in Tables I and II.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study flow diagram depicting the identification of the studies is shown in Figure 1. We identified a total of 1697 potential articles (450 from PubMed; 546 from Embase; 52 from CENTRAL; 631 from Web of Science; and 18 from the reference lists), of which 13 studies including a total of 2,488 THAs fulfilled the inclusion criteria for final review (9, 15-16-17, 19-20-21-22-23-24-25-26-27). The characteristics of the included studies are shown in Tables I and II.…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly reported functional outcome of primary THA was the Harris Hip Score (HHS). A total of 10 studies reported the preoperative, postoperative HHS or the improvement of HHS (9, 16, 19-20-21-22-23-24, 26, 27). All of these studies had observed no significant difference in HHS between CoC and CoP THAs.…”
Section: Resultsmentioning
confidence: 99%